1993
DOI: 10.1002/tox.2530080207
|View full text |Cite
|
Sign up to set email alerts
|

Biological and chemical aspects of differences in sensitivity of natural populations of aquatic bacterial communities exposed to copper

Abstract: Bacterial populations from the main stream of the River Rhine and its plume in the North Sea, the lower course of the rivers Meuse and Scheldt, and various stagnant waters in the Netherlands were exposed to additions of copper in order to analyze differences in sensitivity. Growth rate, measured as thymidine incorporation rate, was generally more sensitive to copper (EC50: 25–310 μg · L−1) than extracellular phosphatase activity, measured as hydrolysis of methylumbelliferin phosphate (EC50: 179–3000 μgl−1). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Chemical methods, like the measurements of pore-water concentrations or easily extractable fraction of metals, are not providing the solution for accurate prediction of toxic effects at polluted sites [3]. Simple pore-water concentrations are not very helpful in predicting toxic effects of metals because the presence of organic and inorganic complexes and other cations have a pronounced effect on true exposure and therefore on toxicity [4,5]. Therefore, a detailed chemical analysis is needed to predict toxic effects from pore-water concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical methods, like the measurements of pore-water concentrations or easily extractable fraction of metals, are not providing the solution for accurate prediction of toxic effects at polluted sites [3]. Simple pore-water concentrations are not very helpful in predicting toxic effects of metals because the presence of organic and inorganic complexes and other cations have a pronounced effect on true exposure and therefore on toxicity [4,5]. Therefore, a detailed chemical analysis is needed to predict toxic effects from pore-water concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…The biological toxicity of heavy met-al complexes has also been reported, such as the secretion of copper and algae, copper and citric acid, and ethylenediamine complexes. Tubbing et al (1993) confirmed that regardless of how high the EDTA concentration is, a small amount of copper can cause changes in the structure and function of bacteria and algae. All these findings show that the EDTA complex copper is also toxic to bacteria and algae.…”
Section: Organic Mattermentioning
confidence: 78%